2000
DOI: 10.1523/jneurosci.20-08-03033.2000
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity Relating to Generation and Representation of Galvanic Skin Conductance Responses: A Functional Magnetic Resonance Imaging Study

Abstract: Central feedback of peripheral states of arousal influences motivational behavior and decision making. The sympathetic skin conductance response (SCR) is one index of autonomic arousal. The precise functional neuroanatomy underlying generation and representation of SCR during motivational behavior is undetermined, although it is impaired by discrete brain lesions to ventromedial prefrontal cortex, anterior cingulate, and parietal lobe. We used functional magnetic resonance imaging to study brain activity assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
436
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 711 publications
(467 citation statements)
references
References 39 publications
27
436
2
2
Order By: Relevance
“…Since the ACC was not among these regions, it is less likely to be predictive of Lie. Remarkably, the somatosensory association area (BA 40) and the insulae have been associated with the electrodermal response [Critchley et al, [2000]; Tranel and Damasio, [1994]]. In our experiment the insulae were activated in both Lie and Truth contrasts, but the activation in the Lie-Repeat contrast was anterior to the Truth-Lie contrast.…”
Section: Discussionsupporting
confidence: 40%
“…Since the ACC was not among these regions, it is less likely to be predictive of Lie. Remarkably, the somatosensory association area (BA 40) and the insulae have been associated with the electrodermal response [Critchley et al, [2000]; Tranel and Damasio, [1994]]. In our experiment the insulae were activated in both Lie and Truth contrasts, but the activation in the Lie-Repeat contrast was anterior to the Truth-Lie contrast.…”
Section: Discussionsupporting
confidence: 40%
“…Moreover, because previous research already showed that skin conductance responses predicted the PES (Hajcak, McDonald, & Simons, 2003a), we additionally surmised that anxious arousal (Critchley, Elliott, Mathias, & Dolan, 2000;Lang, Greenwald, Bradley, & Hamm, 1993), but not worry, could influence (i.e., augment) PES in our experiment. In other words, while we hypothesized that worry could interfere with the rapid affective tagging of actions selectively, we reckoned that anxious arousal could increase PES specifically, revealing a functional dissociation between these two components of anxiety during action monitoring.…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, the amygdala is not believed to be a necessary neural component underlying normal SCR fluctuations, as lesion data have shown that amygdala patients show intact SCR patterns (Tranel & Damasio, 1993, 1989. Furthermore, functional neuroimaging studies (Critchley, Elliot, Mathias, & Dolan, 2000;Patterson, Ungerleider, & Bandettini, 2002) investigating brain regions important for the general production and maintenance of SCR do not observe amygdala activity.…”
Section: Discussionmentioning
confidence: 99%